1998
DOI: 10.1097/00000542-199812000-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Local Addition of Tenoxicam Reduces the Incidence of Low Back Pain after Lumbar Epidural Anesthesia 

Abstract: In summary, the local addition of tenoxicam reduced the incidence and severity of postepidural backache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…67 In their second study, the addition of tenoxicam to the lidocaine for skin infiltration not only decreased the incidence of back pain after epidural anesthesia but also shortened the duration of the pain. 68 In their third study, the addition of ketoprofen, a more lipid-soluble antiinflammatory drug, to the lidocaine for skin infiltration also reduced the incidence and decreased the severity of back pain after epidural anesthesia. 69 It is tempting to impart a high evidence score because the studies were randomized, controlled, and double blinded.…”
Section: Prevention Of Back Pain From Neuraxial Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…67 In their second study, the addition of tenoxicam to the lidocaine for skin infiltration not only decreased the incidence of back pain after epidural anesthesia but also shortened the duration of the pain. 68 In their third study, the addition of ketoprofen, a more lipid-soluble antiinflammatory drug, to the lidocaine for skin infiltration also reduced the incidence and decreased the severity of back pain after epidural anesthesia. 69 It is tempting to impart a high evidence score because the studies were randomized, controlled, and double blinded.…”
Section: Prevention Of Back Pain From Neuraxial Injectionmentioning
confidence: 99%
“…Controlled studies evaluating the prevention of back pain after neuraxial anesthesia involved mostly the use of an anti-inflammatory medication or steroid, given epidurally or as part of the intradermal injectate. Wang et al 67,68 and Wang and coworkers 69 performed a series of studies wherein they added a steroid into their epidural injectate or added an anti-inflammatory medication to the local anesthetic for skin infiltration. In their first study, they noted that the addition of 5 mg dexamethasone to the epidural anesthesia resulted in a significantly lower incidence of back pain at 24, 48, and 72 hours after the epidural anesthesia (Table 8).…”
Section: Prevention Of Back Pain From Neuraxial Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, introducing an epidural needle or catheter and administering a volume of local anesthetic may result in localized musculoligamentous trauma, hematoma, or inflammation, including periostitis, tendonitis, or osteochondritis, which may be followed by secondary paraspinous muscle spasm. Mild or moderate low back pain is a common complaint after epidural analgesia or anesthesia [7,8]. However, the low back pain that developed in our patients was far more severe than that which often develops in patients undergoing epidural analgesia.…”
Section: Discussionmentioning
confidence: 56%
“…The results of these studies demonstrated that there is evidence for a clinically relevant peripheral analgesic effect of wound infiltration with NSAIDs (29,30).…”
Section: Discussionmentioning
confidence: 93%